Escola de 1º grau Santo Estêvão Diácono: um estudo histórico (1974-2005) - Oliveira, Franciscarla Casimiro de (2015)
Considering the perspective that there are links between sciences, and, the flexibility that the New Cultural History allows the historian, so he can venture into topics that didn't were his own, this study relates History and Education by analyzing the historical processes that have permeated the history of the former school Santo Estevão Diácono, located in the city named as Caicó/RN. The objective was to problematize and to historicize this institution by exposing its foundation, its location change, its name change and, therefore, to provide the school community a reading of their local history by using their practices and experiences as social actors within the context of this community they belong to. We try to show how its founder identity reflects in the school through its assistentialist actions; the education prospects that were worked back then; and seek to establish such school environment through some of its former teachers memories.